Federally Qualified Health Center Penetration Associated With Reduced Community COVID-19 Mortality in Four United States Cities - Mary M. Ford; Angela Allard; Jordan Goldberg; Cynthia Summers (SAGE Publishing, 2022)
Background: The COVID-19 pandemic has had significant impacts on health care access and delivery, with disparate effects across social and racial lines. Federally Qualified Health Centers (FQHCs) provide critical primary care services to the nation's most underserved populations, including many communities hardest hit by COVID-19. Methods: We conducted an ecological analysis that aimed to examine FQHC penetration, COVID-19 mortality, and socio-demographic factors in 4 major United States cities: New York, New York; Chicago, Illinois; Detroit, Michigan; and Seattle, Washington. Results: We found the distribution of COVID-19 cases and mortality varied spatially and in magnitude by city. COVID-19 mortality was significantly higher in communities with higher percentages of low-income residents and higher percentages of racial/ethnic minority residents. FQHC penetration was protective against increased COVID-19 mortality, after model adjustment. Conclusions: Our study underpins the critical role of safety-net health care and policymakers must ensure investment in long-term sustainability of FQHCs, through strategic deployment of capital, workforce development, and reimbursement reform.